2021
DOI: 10.1002/anie.202100451
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Structure and Function of Redox Intermediates in [NiFe]‐Hydrogenases by an Advanced Experimental Approach for Solvated, Lyophilized and Crystallized Metalloenzymes

Abstract: To study metalloenzymes in detail, we developed a new experimental setup allowing the controlled preparation of catalytic intermediates for characterization by various spectroscopic techniques. The in situ monitoring of redox transitions by infrared spectroscopy in enzyme lyophilizate, crystals, and solution during gas exchange in a wide temperature range can be accomplished as well. Two O2‐tolerant [NiFe]‐hydrogenases were investigated as model systems. First, we utilized our platform to prepare highly concen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 61 publications
(159 reference statements)
1
23
0
Order By: Relevance
“…A combination of XANES and EXAFS spectra has shown a similar (and crucially, intact) iron coordination environment for the [4Fe4S] subsite of the H-cluster in the freeze dried and in anoxic solution 35 . Likewise, Lorent et al have demonstrated equivalent activity after lyophilization and reconstitution of O 2 -tolerant [NiFe]-hydrogenases to freshly isolated enzyme, indicating that metal cofactors and amino acid side-chains responsible for proton/electron transfer were not altered by lyophilization' 36 . While most work to date on FeS proteins using Mössbauer spectroscopy has examined frozen biological samples [37][38][39] , these considerations, coupled with earlier work on freeze-dried iron-oxide nanoparticles 40 , and the findings reported below, suggest that lyophilization of prebiotic FeS clusters is an appropriate, if not yet fully validated, methodology.…”
Section: Resultsmentioning
confidence: 99%
“…A combination of XANES and EXAFS spectra has shown a similar (and crucially, intact) iron coordination environment for the [4Fe4S] subsite of the H-cluster in the freeze dried and in anoxic solution 35 . Likewise, Lorent et al have demonstrated equivalent activity after lyophilization and reconstitution of O 2 -tolerant [NiFe]-hydrogenases to freshly isolated enzyme, indicating that metal cofactors and amino acid side-chains responsible for proton/electron transfer were not altered by lyophilization' 36 . While most work to date on FeS proteins using Mössbauer spectroscopy has examined frozen biological samples [37][38][39] , these considerations, coupled with earlier work on freeze-dried iron-oxide nanoparticles 40 , and the findings reported below, suggest that lyophilization of prebiotic FeS clusters is an appropriate, if not yet fully validated, methodology.…”
Section: Resultsmentioning
confidence: 99%
“…This advantage contrasts strongly with the reduction of [NiFe] hydrogenase crystals by H 2 which generates complex mixtures of states that are less suitable for structure determination. 10,25 Manipulation of pH offers a further dimension to the control over speciation of the crystalline enzyme. Such control offers a more rational approach to obtaining structures for catalytic intermediates than has previously been possible and eliminates the need for low activity variants, 75 inhibitors, 76 or transition-state analogues 77 that have been mainstays of classical (pre-XFEL) time-resolved structure determination from single crystals.…”
Section: Resultsmentioning
confidence: 99%
“… 7–9 Methods for studying crystalline and lyophilised enzyme using gas exchange have also been reported. 10 Verification of protein redox states in crystallo presents a further challenge, and to this end, a number of synchrotron macromolecular crystallography beamlines have introduced microspectroscopic methods for secondary characterisation of protein crystals, including UV-visible and Raman spectroscopy. 11–13 …”
Section: Introductionmentioning
confidence: 99%
“…A mechanism for the removal of the bridging OH ligand from the N i r-S inactive ready state upon irradiation has been suggested 51 . Re-activation can also be triggered by light under cryogenic conditions in the protein crystals 52 . We are not aware of any evidence that NiFe hydrogenases are damaged upon irradiation.…”
Section: Introductionmentioning
confidence: 99%